Characterization of a hospital outbreak of imipenem-resistant Acinetobacter baumannii by phenotypic and genotypic typing methods. - Tankovic, J (1994)
During a 13-month period, 31 patients hospitalized primarily in two intensive care units (ICUs) were either colonized or infected by imipenem-resistant Acinetobacter baumannii. Typing of the isolates by three methods (antibiotyping, biotyping, and pulsed-field gel electrophoresis) revealed that two distinct strains were involved in the first 9 cases of the outbreak and that one of these strains, which had acquired a higher level of imipenem resistance as well as resistance to all aminoglycosides, accounted for 21 of 22 cases in the second part of the outbreak. ICU environmental contamination was recognized as an important reservoir of this epidemic strain. The outbreak ceased only after the ICUs were closed for complete cleaning and disinfection.